Influence of Dental Pain and Tooth Sensitivity on the Intention to Quit Smoking among Schoolchildren - Muhammad Nazir; Hassan AlAbdullah; Muhanad Alhareky; Asim Al-Ansari; Jehan Alhumaid (Hindawi Limited, 2020)
Objective. To evaluate the association between oral health problems and sociodemographic factors with the intention to quit smoking and join the tobacco cessation program among schoolchildren. Materials and Methods. This cross-sectional study included a sample of 10-12 grade male students from public high schools in different cities of the Eastern province of Saudi Arabia. Schoolchildren responded to a pilot-tested questionnaire about self-reported oral health problems and the intention to quit smoking. Bivariate and multivariate logistic regression analyses were performed. Results. Out of 587 schoolchildren, 199 were smokers with a smoking prevalence of 33.9%. Significantly higher proportions of smokers than nonsmokers had tooth sensitivity (P = 0.029) and dryness of the mouth (P = 0.001). Most smokers (75.9%) had a family history of smoking, and 51.8% started smoking within the last two years. Tooth sensitivity (56.3%), dental cavities (52.8%), and dental pain (44.7%) were highly prevalent among smokers. About one-third of smokers expressed their intention to quit smoking (38.2%) and join a smoking cessation program (33.7%). Tooth sensitivity (OR = 3.7, P = 0.004) and dental pain (OR = 2.84, P = 0.014) were significantly associated with quitting smoking. In addition, smokers with tooth sensitivity (OR = 3.22, P = 0.007) had higher odds of joining a smoking cessation program than those without tooth sensitivity. The smokers who started smoking within the last two years (OR = 3.97, P = 0.002) were more likely to quit smoking than those who initiated smoking for more than two years. Conclusion. Oral health problems were highly prevalent among smokers. Tooth sensitivity was significantly associated with quitting smoking and joining a cessation program in children. The awareness about the adverse effects of smoking on oral health should be part of regional, national, and global tobacco prevention policies and programs.